The Microbiota and Epigenetic Regulation of T Helper 17/Regulatory T Cells: In Search of a Balanced Immune System - Luo, Annie; Leach, Steven T.; Barres, Romain; Hesson, Luke B.; Grimm, Michael C.; Simar, David (Frontiers in Immunology, 2017)
Immune cells not only affect tissue homeostasis at the site of inflammation but also exert systemic effects contributing to multiple chronic conditions. Recent evidence clearly supports an altered Th17/Treg (T helper 17/regulatory T cell) balance leading to the development and progression of inflammatory diseases that not only affect the gastro-intestinal tract but that also have whole body manifestations, including insulin resistance. Epigenetic mechanisms are amenable to both environmental and circulating factors and contribute to determining the T cell landscape. The recently identified participation of the gut microbiota in the remodeling of the epigenome of immune cells has triggered a paradigm shift in our understanding of the aetiology of various inflammatory diseases and opened new paths towards therapeutic strategies. In this review, we provide an overview of the contribution of the Th17/Treg balance in the development and progression of inflammatory bowel diseases (IBD) and metabolic diseases. We discuss the involvement of epigenetic mechanisms in the regulation of T cell function in the particular context of dysbiosis. Lastly we examine the potential for nutritional interventions affecting the gut microbiota to reshape the T cell epigenome and address the inflammatory component of various diseases.